HUBUNGAN KREATIVITAS GURU PADA MATA PELAJARAN IPAS DENGAN MINAT BELAJAR SISWA KELAS V SD NEGERI 207 APALA KECAMATAN BAREBBO KABUPATEN BONE - Kadir, Abd; Nurul, Nurul Hidayah; Rahmi, Sitti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research analyzes the relationship between teacher creativity in the subjects of science and natural sciences with the learning interests of fiffth grade students of SD Negeri 207 Apala, Barebbo District, Bone Regency. The purpose of this study was to determine whether or not there was a significant relationship between theacher creativity in the subject of science and natural sciences with the learning interests of fifth grade students of SD Negeri 207 Apala. The approach used in this study was a quantitative approach with a correlational research type. The data sources in this study were all fifth grade students of SD Negeri 207 Apala, totaling 21 students. The data collection technique uses a questionnaire. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of teacher creativity research obtained an average of 74.05 in the medium category, while student interest in learning obtained an average of 78.19 in the medium category. The results of the inferential statistical analysis of the Spearman correlation were 0.752 with a strong category because it was in the range 0.60-0.799. Based on the results of inferential statistical analysis, it shows that the significant value is 0.000, which means <0.05. Thus, H0 is rejected and H1 is accepted with a correlation coefficient of 0.752, which means it has a positive relationship in the strong category, so it can be concluded that the research results show a significant relationship between teacher creativity in science and science subjects and students' interest in learning in class V of SD Negeri 207 Apala, Barebbo District, Bone Regency.